Estima de lugar e implicações com a saúde: a perspectiva dos usuários de um Centro de Saúde do Nordeste do Brasil [e - Barreto, Elcides Hellen Ferreira Landim (2017)
The present study aims to analyze the esteem of place of citizen-users of a Family Health Center in the Northeast of Brazil and its implications for health. It also seeks to identify affections in the people who use the Family Health Center, which may or may not involve them in a healthy lifestyle, as well as their perceptions about healthy living. The understanding of environmental and human health issues as well as those arising from this relationship are still limited. Thus, it is important and urgent that studies be developed to provide effective ways of understanding and, consequently, intervening in the problems arising from this field. With this aim in mind, this work starts from the fields of Social Psychology, Environmental Psychology and Collective Health of historical-cultural approach to think about the relationships between affectivity, esteem of place and health promotion. In this way, the objective of this study is to broaden these discussions by presenting the esteem of place (BOMFIM, 2010) as a dimension of health, and the implications of a healthy way of life based on the understanding of the subjects-users of Basic Health Care. In order to do so, the IGMA (Affective Maps Generator Instrument) was used in this research to identify the esteem of place of the subjects, and a semi-structured interview to understand the implication with a healthy lifestyle with 41 citizens-users of the Family Health Center Sao Gerardo in Ico (CE). With this study it was possible to identify that the lifestyle considered healthy by the subjects is dictated by technocratic, utilitarian and scientificist logic, in which specific scientific knowledge overlaps popular knowledge as the only one possible. However, the esteem of place of the citizens-users of the health unit proves to be potential and indicative of involvement with the healthy way of life. Thus, it is perceived that although the healthy life is not the result of the autonomy of the subjects, once the relationship between the citizen and the healthy way of life occurs through passivity, the affections related to it are not generators of servitude, but rather, of pleasantness and belonging, therefore full of potential. Thus, it is concluded that health education, as it has been put into practice, has promoted the involvement of the subjects with a healthy way of life, however, not in an emancipatory and autonomous way, but rather in a passive way through the following of a lifestyle prescribed by the ideological power apparatus. With this research, it is hoped to foster an ethical-political discussion that contributes to strengthen the actions of the Family Health Strategy, enabling greater participation of citizens and effectiveness in the implementation of the actions proposed in the National Policy for Health Promotion (PNPS) in order to promote a healthy lifestyle which reveals the autonomy and emancipation of the subjects.